Superior–Subordinate Communication in the Workplace: Verbal Aggression, Nonverbal Immediacy, and Their Joint Effects on Perceived Superior Credibility. Issue 2 (3rd April 2017) - Lybarger, Joseph E.; Rancer, Andrew S.; Lin, Yang
Abstract : This study examined the joint effects of a superior's verbally aggressive behaviors and nonverbal immediacy behaviors on a subordinate's perceptions of a superior's credibility. Participants ( n = 415) from intact classes were randomly assigned into one of the four experiment conditions simulated by four video segments: use of nonverbal immediacy and verbal aggression, nonuse of nonverbal immediacy and use of verbal aggression, use of nonverbal immediacy and nonuse of verbal aggression, and nonuse of nonverbal immediacy and verbal aggression. The findings indicate that superiors who do not use verbally aggressive messages and who are nonverbally immediate were perceived with a higher level of competence, trustworthiness, and caring than superiors who use verbally aggressive messages and who are not nonverbally immediate. In addition, superiors who use verbally aggressive messages and who are nonverbally immediate were perceived with the lowest level of perceived competence as compared to superiors in the other three conditions.